Development of Competency in Early Childhood by Place-Based Learning - Tawkaew, Kanchana (Ratchaphruek Journal, 2025)
This applied research aimed to develop, examine the implementation, and expand the competency enhancement model for early childhood children through place-based learning experiences. The research was conducted in three phases: 1) Preparation, 2) Implementation, and 3) Expansion. The sample group consisted of 12 schools under the Primary Educational Service Area Office Nakhon Ratchasima Zone 1, selected through voluntary participation, comprising 16 administrators, 28 teachers, and 287 students. Statistical analysis included frequency, mean, standard deviation, and content analysis. The research findings revealed that: 1) The development of the competency enhancement model for early childhood children through competency-based learning resulted in a Sandbox curriculum prototype using place-based learning, consisting of learning management characteristics, objectives, Sandbox curriculum development principles, and Sandbox curriculum development guidelines. 2) The implementation of the place-based Sandbox curriculum showed that the Sandbox curriculum promoted children’s creative thinking and collaborative work, while enabling teachers to organize learning experiences effectively. 3) The expansion of the place-based Sandbox curriculum resulted in 12 learning units, enhanced early childhood children’s competencies through creative work production, and enabled teachers to adapt curriculum development according to interests and school contexts.